1996
DOI: 10.1108/09615539610113091
|View full text |Cite
|
Sign up to set email alerts
|

A second order splitting algorithm for thermally‐driven flow problems

Abstract: . (1995). A second order splitting algorithm for thermally-driven flow problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…Minev et al [11] describe a spectral element method for thermal problems that, in many respects, is similar to ours. There are some notable di erences though, both in the methodology and in the application to the cavity problem.…”
Section: Methodsmentioning
confidence: 63%
See 1 more Smart Citation
“…Minev et al [11] describe a spectral element method for thermal problems that, in many respects, is similar to ours. There are some notable di erences though, both in the methodology and in the application to the cavity problem.…”
Section: Methodsmentioning
confidence: 63%
“…As noted in the Introduction, Minev et al [11] reported computational examples of thermal cavity ows obtained by a spectral element method. In that work only the Nusselt numbers were reported, and the heat ux at the wall was computed by ÿrst-order ÿnite di erences.…”
Section: Square Cavity Simulationsmentioning
confidence: 97%
“…Numerical simulation has been applied to this kind of flows and results with a 2D Direct Numerical Simulation (DNS) have been reported in [5] and [6]. For the validation of our results we are comparing them with those reported in the cited bibliography.…”
Section: Introductionmentioning
confidence: 92%
“…To achieve a conclusion about the approximation quality ofp n+1 h we compare the right sides of (20) and (22). The derivations on the right side in (22) can be built with a kind of gradient recovery technique to achieve a higher order with the effects discussed above.…”
Section: Motivation For the Multi-grid Postprocessingmentioning
confidence: 99%
“…[26,18]. For the boundary conditions of the second-order pressure equation we refer to the discussion in the papers of Karniadakis et al [16], Maday et al [19] and Timmermanns et al [20,23]. For the computation of the pressure boundary conditions in Section 2 we used a variation of the formulation given in [16] by Karniadakis. To use this technique we have to evaluate the laplacian operator with linear finite elements, which leads to a couple of problems that can be avoided using a gradient recovery technique.…”
Section: Introductionmentioning
confidence: 99%